1999
DOI: 10.1111/j.1574-695x.1999.tb01351.x
|View full text |Cite
|
Sign up to set email alerts
|

F1651fimbriae of the P fimbrial family inhibit the oxidative response of porcine neutrophils

Abstract: The F165(1) fimbrial system has been associated with the resistance of Escherichia coli O115:K"V165" to phagocytic killing by porcine polymorphonuclear leukocytes (PMNLs). One mechanism of this resistance seemed to be inhibition of the oxidative response as observed following induction of PMNLs by phorbol myristate acetate (PMA) and treatment with bacteria possessing the F165(1) fimbriae. In order to confirm whether or not the F165(1) fimbriae are involved in this inhibition, we evaluated the effect of F165(1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…The regulatory region of foo shares more than 96% identity with that of the pyelonephritis-associated pili (pap) gene. Previous work showed that F165 1 fimbriae are essential for virulence and survival during systemic stages of infection in young pigs (5)(6)(7)(8). F165 1 fimbriae are principally found in infections caused by opportunistic E. coli in animals, while Pap fimbriae are found in human clinical cases of urinary tract infections.…”
mentioning
confidence: 99%
“…The regulatory region of foo shares more than 96% identity with that of the pyelonephritis-associated pili (pap) gene. Previous work showed that F165 1 fimbriae are essential for virulence and survival during systemic stages of infection in young pigs (5)(6)(7)(8). F165 1 fimbriae are principally found in infections caused by opportunistic E. coli in animals, while Pap fimbriae are found in human clinical cases of urinary tract infections.…”
mentioning
confidence: 99%